Fuel utilization effects on system efficiency in solid oxide fuel cell gas turbine hybrid systems. (15th October 2018) - Oryshchyn, Danylo; Harun, Nor Farida; Tucker, David; Bryden, Kenneth M.; Shadle, Lawrence
Graphical abstract: Highlights: SOFC-GT hybrids were designed for various levels of SOFC fuel utilization, Uf . System efficiency was high, >70% LHV, between 65 and 90% Uf using syngas fuel. Lower Uf increased the Nernst potential and GT inlet T, while SOFC size dropped. Peak efficiency was found with SOFC only providing 65% of the power share. Hybrid designs with 40–60% output power from SOFC had comparable economics. Abstract: A computational analysis was conducted to optimize the design of a solid oxide fuel cell - gas turbine hybrid power generator, focusing on the impact that fuel utilization within the fuel cell has on system efficiency and installed costs. This is the first ever design-study considering the effect of fuel utilization on performance, as well as on the optimum power split. This hybrid system attained high electric generation efficiencies (>70%) over a wide range of operating conditions (60% < fuel utilization < 90%) while the fuel cell stack size decreased in proportion to decreasing the fuel utilization. A one-dimensional fuel cell model was used to simulate the fuel cell while GateCycle® was used to simulate the performance of the associated recuperated turbine and various subsystems necessary for thermal management. For each test case, the size of the solid oxide fuel cell, gas turbine, and recuperator, as well as the fuel and air flow rates, hot-air bypass set point, and heat exchange effectiveness in the solid oxide fuel cell manifold were varied to obtain 550 MWe output. In addition, anode recycle, turbomachinery efficiency, and various thermal management options were tested. The maximum system efficiency (75.6%) was attained for the single-pass solid oxide fuel cell with highly efficient turbomachinery when the solid oxide fuel cell used 80% of the incoming fuel. Efficiency was essentially flat from 75% fuel utilization through 85% fuel utilization. Employing anode recycle starting at 65% resulted in roughly 1 percentage point efficiency decrease for each percent increase in fuel utilization. For minimized solid oxide fuel cell degradation, a near 50:50 power split case was studied resulting in 68.6% efficiency and the solid oxide fuel cell using 55% of the incoming fuel. Because of shifting half of the power generation to the gas turbine, the size of the fuel cell stack was reduced by 25% as compared to that at maximum efficiency (80% fuel utilization).